INTERACTIVE METHODS AND THEIR USE IN EDUCATIONAL ACTIVITIES (International journal of artificial intelligence, 2026)
This article discusses the essence of interactive methods, their role in the educational process, and their effectiveness in modern teaching. It also analyzes the types of interactive methods, ways of applying them during lessons, and their importance in developing students’ independent thinking skills. The article highlights that the use of interactive methods in education helps improve learners’ activity, creativity, communication abilities, and overall learning outcomes.